2023
DOI: 10.1007/s12265-023-10379-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Animal Models for Investigating Cardioprotective Roles of SGLT2 Inhibitors

Abstract: Sodium-glucose co-transporter 2 (SGLT2) inhibitors represent one type of new-generation type 2 diabetes (T2DM) drug treatment. The mechanism of action of an SGLT2 inhibitor (SGLT2i) in treating T2DM depends on lowering blood glucose levels effectively via increasing the glomerular excretion of glucose. A good number of randomized clinical trials revealed that SGLT2is significantly prevented heart failure (HF) and cardiovascular death in T2DM patients. Despite ongoing clinical trials in HF patients without T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In mouse models of heart failure, administration of SGLT2i has been found to induce anti-inflammatory effects on the heart without any changes in the levels of circulating ketone bodies or cardiac ATP production, suggesting a more direct involvement. Specifically, a lower cardiac and peripheral activation of NLRP3 inflammasome and ROS production was observed [27]. In parallel, other studies on similar murine models have demonstrated cardiac benefits, such as prevention of ejection fraction reduction, improved diastolic function, and reduced wall stress, without significant changes in fibrosis processes, suggesting that anti-fibrotic effects are not necessarily correlated [28,29].…”
Section: Oxidative Stress Inflammation Cardiac Fibrosis and Remodelingmentioning
confidence: 60%
“…In mouse models of heart failure, administration of SGLT2i has been found to induce anti-inflammatory effects on the heart without any changes in the levels of circulating ketone bodies or cardiac ATP production, suggesting a more direct involvement. Specifically, a lower cardiac and peripheral activation of NLRP3 inflammasome and ROS production was observed [27]. In parallel, other studies on similar murine models have demonstrated cardiac benefits, such as prevention of ejection fraction reduction, improved diastolic function, and reduced wall stress, without significant changes in fibrosis processes, suggesting that anti-fibrotic effects are not necessarily correlated [28,29].…”
Section: Oxidative Stress Inflammation Cardiac Fibrosis and Remodelingmentioning
confidence: 60%
“…Even though the clinical literature to support the use of SGLT-2 inhibitors is increasing, the mechanism through which these agents act on the myocardium to produce improved outcomes over the long term remains poorly understood [ 14 , 15 , 16 ]. Small animal models using rodents have demonstrated increased cardiac output, decreased myocardial remodeling, reduced oxidative stress, and improved vascular reactivity in both acute ischemia and reperfusion injury and in healthy myocardium [ 9 , 17 , 18 ]. Owing to the heterogeneity between small animal models and the patients they are designed to represent, however, these models are unable to fully recapitulate the features of adult CVD and, thus, fall short of the explanatory power needed to fully understand the effects of SGLT-2 inhibitors in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is growing interest in the use of novel diabetic medications in the management of CAD. Several agents including sodium‐glucose transport protein 2 (SGLT‐2) inhibitors and glucagon‐like peptide 1 (GLP‐1) receptor agonists have shown significant promise in treating patients with CAD and heart failure in both pre‐clinical and clinical studies (Al Thani et al., 2023 ; Bhagavathula et al., 2021 ; McMurray et al., 2019 ; Sabe, Xu, et al., 2023 ; Wiviott et al., 2019 ). This growing body of evidence has resulted in guideline changes favoring the use of GLP‐1 agonist and SGLT‐2 inhibitors ( Circulation , 2022 ; Knuuti et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%